Analisis Pelanggaran Etika dan Kode Etik Profesi Akuntan Di Era Persaingan Yang Kompetitif : Studi Kasus PT Indofood Tbk - Farin Aprita; Savina Dwi Cahya; Anisa Yulianti; Nadia Nadia; Tri Gianti; Saridawati Saridawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Accountant Code of Ethics is a guideline to regulate the ethics of the Indonesian public accounting profession in order to fulfil professional responsibilities. IAMI, IAI and IAPI. Based on the research of this scientific article, the author conducted research observations on Business Ethics in the Digital Age. The object of research comes from literature such as google scholar, online media, and company reports of PT Indofood Tbk. The purpose of this article is to find out violations of the ethics and code of ethics of the accounting profession at PT Indofood. Based on the case study described above related to PT Indofood, Tbk which has violated the code of ethics. Indomie products contain harmful substances that will harm consumers if they consume these products. PT Indofood Tbk. has violated the principle of honesty in business ethics by not informing its customers about the dangerous content in their products.